Clinical presentation, diagnosis and staging of cholangiocarcinoma. (25th March 2019) - Forner, Alejandro; Vidili, Gianpaolo; Rengo, Marco; Bujanda, Luis; Ponz‐Sarvisé, Mariano; Lamarca, Angela
Abstract: Cholangiocarcinoma (CCA) is a heterogeneous group of tumours, derived from cells of the biliary tree, which represent the second most frequent primary liver tumour. According to the most recent classifications, CCA can be subdivided into intrahepatic (iCCA) and extrahepatic (eCCA) which include perihilar (pCCA) and distal (dCCA) CCA. CCA are usually identified at advanced stages, when the primary tumour grows enough to produce a large liver mass or when jaundice has developed because of biliary tree obstruction. The ongoing challenges in the identification of risk factors and definition of a specific population at higher risk of developing CCA are the main challenges for the development of screening programs. Therefore, late diagnosis remains an unresolved issue in CCA. Imaging plays an important role in the detection and characterization of CCA, helping with radiological diagnosis, guiding biopsy procedures and allowing staging of the tumour. This review focuses on clinical presentations and diagnosis and staging techniques of CCA.